Valuasi Ekonomi Sungai Trokon di Kabupaten Rejang Lebong - Syahlahudhin Al Ayufhi; Benny Pratama; Abdurrahman Suwardi; Reflis Reflis; Satria Putra Utama (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to estimate the economic value of the Trokon River in Rejang Lebong Regency as a natural resource with both ecotourism potential and essential ecological functions. The research applies the Contingent Valuation Method (CVM) using a Willingness to Pay (WTP) approach to determine how much visitors and local residents are willing to contribute to the conservation of the river. Data were collected through questionnaires distributed to 100 respondents, consisting of tourists and local community members. The results show that the average WTP is IDR 12,000 per visit, with a total estimated economic value of IDR 60,000,000 per year. Significant factors influencing WTP include income level, frequency of visits, and environmental awareness. These findings indicate that the Trokon River holds considerable economic value that should be integrated into community-based conservation management. The study recommends implementing a voluntary conservation fee system and strengthening local institutions to support sustainable management.